Introducing Pitt-Hopkins syndrome-associated mutations of TCF4 to Drosophila daughterless. - Tamberg, L.; Sepp, M.; Timmusk, T.; Palgi, M. (Biology open, 2015)
Pitt-Hopkins syndrome (PTHS) is caused by haploinsufficiency of Transcription factor 4 (TCF4), one of the three human class I basic helix-loop-helix transcription factors called E-proteins. Drosophila has a single E-protein, Daughterless (Da), homologous to all three mammalian counterparts. Here we show that human TCF4 can rescue Da deficiency during fruit fly nervous system development. Overexpression of Da or TCF4 specifically in adult flies significantly decreases their survival rates, indicating that these factors are crucial even after development has been completed. We generated da transgenic fruit fly strains with corresponding missense mutations R578H, R580W, R582P and A614V found in TCF4 of PTHS patients and studied the impact of these mutations in vivo. Overexpression of wild type Da as well as human TCF4 in progenitor tissues induced ectopic sensory bristles and the rough eye phenotype. By contrast, overexpression of Da(R580W) and Da(R582P) that disrupt DNA binding reduced the number of bristles and induced the rough eye phenotype with partial lack of pigmentation, indicating that these act dominant negatively. Compared to the wild type, Da(R578H) and Da(A614V) were less potent in induction of ectopic bristles and the rough eye phenotype, respectively, suggesting that these are hypomorphic. All studied PTHS-associated mutations that we introduced into Da led to similar effects in vivo as the same mutations in TCF4 in vitro. Consequently, our Drosophila models of PTHS are applicable for further studies aiming to unravel the molecular mechanisms of this disorder.